2018
DOI: 10.1177/1535370218806828
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miR-708-5p in peripheral blood monocytes: Potential marker for postmenopausal osteoporosis in Mexican-Mestizo population

Abstract: Osteoporosis is the most frequent disorder of bone metabolism, owing to an alteration between osteoclast and osteoblast activity, which results from the interaction of genetic, environmental, and epigenetic factors. microRNAs, small non-coding RNAs of around 22 nucleotides with important regulatory roles in gene regulation, that target mRNAs for post-transcriptional destabilization have been suggested as biomarkers in several disorders. In this work, we used small RNA sequencing to identify microRNAs from peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
2
8
1
Order By: Relevance
“…Rafael et al. 23 previously detected the up-regulation of miR-708-5p in peripheral blood mononuclear cells of Mexican osteoporotic women, but we did not observe this in the osteoclast induction of BMMs. Therefore, future work should use PBMCs as the precursor to induce osteoclasts to detect changes in miR-708-5p expression because miRNAs in precursor cells from different sources may have different trends.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Rafael et al. 23 previously detected the up-regulation of miR-708-5p in peripheral blood mononuclear cells of Mexican osteoporotic women, but we did not observe this in the osteoclast induction of BMMs. Therefore, future work should use PBMCs as the precursor to induce osteoclasts to detect changes in miR-708-5p expression because miRNAs in precursor cells from different sources may have different trends.…”
Section: Discussioncontrasting
confidence: 97%
“…Dozens of miRNAs are considered to play a role in osteoporosis, 22 but the regulatory role of miR-708-5p and miR-708-3p in osteoporosis has rarely been reported. De-La-Cruz-Montoya et al 23 showed for the first time that miR-708-5p was up-regulated in peripheral blood mononuclear cells of Mexican women with osteoporosis, and could be used as a marker for osteoporosis. Of note, miR-708-5p and miR-708-3p are processed from the same pre-miRNA, while miR-708-3p usually exists as a passenger strand (miRNA*) and more studies focus on mir-708-5p as a guide-strand.…”
Section: Discussionmentioning
confidence: 99%
“…The same research team [ 80 ] identified four upregulated miRNAs (miR-708-5p, miR-34b-5p, miR-3161, and miR-328-5p) and two downregulated miRNAs (miR-4422 and miR-939-3p) in monocytes isolated from peripheral blood of seven OP patients, compared with seven HC, by using small RNA-sequencing. Following qPCR validation, only miR-708-5p was found significantly upregulated in OP women.…”
Section: Mirnas In Human Circulating Monocytesmentioning
confidence: 99%
“…Interestingly, some of the miRNAs detected in this network have been already demonstrated to regulate differentiation processes. For instance, it has been reported that, in peripheral blood monocytes, miR-708-5p can negatively regulate the expression level of factors involved in bone metabolism such as AKT1, AKT2, PARP1 FKBP5, and MP2K3, resulting in an osteoporotic phenotype [ 39 ]. Moreover, the lncRNA HIF1A-AS2 can competitively bind miR-665 and thus positively regulates IL6, activating the PI3K/Akt signaling pathway, which promotes osteogenic differentiation of adipose-derived stem cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%